2021
DOI: 10.1007/s12529-021-09967-z
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Psychological Risk Factors for Anxiety and Depression: Findings from the Covid-19 Health and Adherence Research in Scotland on Mental Health (CHARIS-MH) Cross-sectional Survey

Abstract: Background Investigations about mental health report prevalence rates with fewer studies investigating psychological and social factors influencing mental health during the Covid-19 pandemic. Study aims: (1) identify sociodemographic groups of the adult population at risk of anxiety and depression and (2) determine if the following social and psychological risk factors for poor mental health moderated these direct sociodemographic effects: loneliness, social support, threat perception, illness re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 48 publications
8
52
0
4
Order By: Relevance
“…Although a thorough recruitment strategy was adopted, this sample was the relatively highly educated, less deprived, and physically active compared to the Scottish population at large, Thus, finding that some had difficulties due to COVID-19 social distancing among this group suggests that these effects may be even worse for those in lower socioeconomic groups and/or who are less active. This finding is in line with that of a previous survey which showed that poorer wellbeing was reported among women and more deprived groups [30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although a thorough recruitment strategy was adopted, this sample was the relatively highly educated, less deprived, and physically active compared to the Scottish population at large, Thus, finding that some had difficulties due to COVID-19 social distancing among this group suggests that these effects may be even worse for those in lower socioeconomic groups and/or who are less active. This finding is in line with that of a previous survey which showed that poorer wellbeing was reported among women and more deprived groups [30].…”
Section: Discussionsupporting
confidence: 93%
“…This shows some positive outcomes from this research, as older adults who increased or maintained the size and/or quality of their social networks had better social support and lower loneliness [ 17 ]. This is somewhat in line with a previous survey where the wellbeing of older adults was less influenced by loneliness than that of younger adults, perhaps underlining the greater contrast between pre-pandemic and current pandemic social contact for younger people [ 30 , 31 , 32 ]. However, a substantial proportion here still did report high levels of loneliness despite this social contact, and social support scores were slightly lower than normative values [ 46 ], underlining the importance of addressing this issue among older adults too.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hubard et al. showed that anxiety and depression are associated with social (social support, loneliness), sociodemographic (age, gender, deprivation), and psychological factors (perceived threat and illness representations) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of this is new to society, and of course causes a variety of reactions, where each individual will react in conveying his or her concerns, and people will react individually and collectively. (25,26) Several reviews reported the psychological symptoms that were found. A recent review of psychological symptoms in individuals undergoing quarantine includes stress, depression, irritability, insomnia, fear, confusion, anger, frustration, boredom and stigma associated with quarantine, and some of these psychological conditions can persist after quarantine.…”
Section: Introductionmentioning
confidence: 99%